2013
DOI: 10.3109/08958378.2013.781250
|View full text |Cite
|
Sign up to set email alerts
|

Source and trajectories of inhaled particles from a surrounding environment and its deposition in the respiratory airway

Abstract: The inhalation exposure to airborne particles is investigated using a newly developed computational model that integrates the human respiratory airway with a human mannequin and at an enclosed room environment. Three free-stream air flow velocities (0.05, 0.20, and 0.35 m s⁻¹) that are in the range of occupational environments are used. Particles are released from different upstream locations and their trajectories are shown, which revealed that the trajectory paths of 80 μm particles that are inhaled are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…There still exist uncertainties concerning the appropriateness of such simplifications because features outside of the nose have a significant effect on airflows and particle behaviors within it (Doorly et al, 2008). A number of numerical studies have considered the external face in estimating particle inhalability in humanoid models (Anthony, 2010;Anthony & Anderson, 2013;Inthavong et al, 2012Inthavong et al, , 2013Li et al, 2012;Se et al, 2010). However, even larger numbers of numerical studies have excluded the facial interface (Liu et al, 2007;Martonen et al, 2003;Schroeter et al, 2001;Shi et al, 2006;Xi & Longest, 2009;Xi et al, 2011;Yu et al, 1998;Zamankhan et al, 2006), partially due to the complexity in developing computational models and the excessive computational expense incurred.…”
Section: Introductionmentioning
confidence: 97%
“…There still exist uncertainties concerning the appropriateness of such simplifications because features outside of the nose have a significant effect on airflows and particle behaviors within it (Doorly et al, 2008). A number of numerical studies have considered the external face in estimating particle inhalability in humanoid models (Anthony, 2010;Anthony & Anderson, 2013;Inthavong et al, 2012Inthavong et al, , 2013Li et al, 2012;Se et al, 2010). However, even larger numbers of numerical studies have excluded the facial interface (Liu et al, 2007;Martonen et al, 2003;Schroeter et al, 2001;Shi et al, 2006;Xi & Longest, 2009;Xi et al, 2011;Yu et al, 1998;Zamankhan et al, 2006), partially due to the complexity in developing computational models and the excessive computational expense incurred.…”
Section: Introductionmentioning
confidence: 97%
“…Studies by Se et al [37] and Inthavong et al [38] investigated the inhalability of particles via a realistic human head and indicated velocity vectors were directed slightly upwards towards the nostril opening, leading to a lower critical area for small particles and a higher critical area for heavy particles. Li et al [39] included a nasal cavity model inside a simplified standing mannequin and placed in a large room.…”
Section: Introductionmentioning
confidence: 99%
“…Individual aspects of the nasal cavity such as the geometry and flow rate collectively affect the airflow patterns and consequently, the transport of particles through the cavity. Significant anatomical factors include the nasal length, the bend from the nostrils into the cavity (Inthavong et al, 2011a(Inthavong et al, , 2013a(Inthavong et al, , 2019, and turbinate structure (Churchill et al, 2004). Xi et al (2016) showed that the nostril inlet orientation has significant influence on eventual particle deposition, as it is the first point of interaction between the inhaled particles and the internal nasal anatomy.…”
Section: Micron Particle Depositionmentioning
confidence: 99%
“…Particle trajectories represented by symbols (10 and 80 μm) and lines (1 and 40 μm) released from different upstream distances away from the nostrils in the x-axis, and at free-stream velocities of (a) U ¥ = 0.05 m/s and (b) U ¥ = 0.35 m/s. Velocity vectors in the background represent the ambient flow field, coloured by its magnitude with red being the peak velocity and blue the minimum velocity(Inthavong et al, 2013a; reproduced with permission © Taylor & Francis 2013).…”
mentioning
confidence: 99%